2004
DOI: 10.1111/j.1525-1594.2004.07382.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Implantable Undulation Type Ventricular Assist Device for Control of Organ Circulation

Abstract: It is well known that a rotary blood pump (RP) is effective as a small ventricular assist device (VAD). It might be still more effective if pulsation was available. The undulation pump (UP), which is a type of small RP, can also produce pulsation. In Japan, a development project for an implantable type UP ventricular assist device (UPVAD) is now advanced. Six universities and some companies together have been in charge of the development project for 5 years. In this study, the influence which the UP under deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the basis of this method, rotary blood pump with undulation pump was used in experiments to evaluate the arterial response to the rotary blood pump assistance (11,12). A healthy adult goat with UPVAD rotary blood pump was used in this experiment and results are shown in Fig.…”
Section: Undulation Pump Ventricular Assist Device (Upvad) and Ptt Chmentioning
confidence: 99%
“…On the basis of this method, rotary blood pump with undulation pump was used in experiments to evaluate the arterial response to the rotary blood pump assistance (11,12). A healthy adult goat with UPVAD rotary blood pump was used in this experiment and results are shown in Fig.…”
Section: Undulation Pump Ventricular Assist Device (Upvad) and Ptt Chmentioning
confidence: 99%
“…They proposed a left ventricular assist device control means which preserves right‐sided circulatory function at all times, while supporting peripheral perfusion. Tomoyuki Yambe et al (29) of the Tohoku University (Tohoku, Japan) reported on the development of an implantable undulation type ventricular assist device for the control of organ circulation. The ability to produce pulsation with this rotary pump suggests the ability to prevent multiple organ failure.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%